Detection, monitoring and mitigation of health risk: a study of high risk detection, monitoring and mitigation: a study of high-cost based on frequency versus severity for social social security - Caparó, Rafael (2018)
Globally, high-cost diseases are generating a loss of social efficiency in a tendential manner, different causes are generated by these diseases, but the consequences for social insurance are reflected in unsustainable increases in costs. This work intends to serve as support to determine which diseases can be considered as high cost based on a frequency versus severity analysis, in such a way that it serves as support in the decision making of health policy makers, although the issue of high-cost diseases goes beyond a quantitative-qualitative model, especially for the health of people, this work aims to serve as a basis for a management of health services based on costs that complement the efficient and particular management of all kinds of high cost diseases.